2014
DOI: 10.1002/mrm.25573
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency configuration to facilitate bilateral breast31P MR spectroscopic imaging and high-resolution MRI at 7 Tesla

Abstract: Purpose: High-resolution MRI combined with phospholipid detection may improve breast cancer grading. Currently, configurations are optimized for either high-resolution imaging or 31 P spectroscopy. To be able to perform both imaging as well as spectroscopy in a single session, we integrated a 1 H receiver array into a 1 H-31 P transceiver at 7T. To ensure negligible signal loss due to coupling between elements, we investigated the use of a floating decoupling loop to enable bilateral MRI and 31 P MRS. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…A wide variety of breast MRI studies at 7 T have been presented with various RF coil setups . Although imaging performance in the anterior part of the breast is generally good, clinical usability might be impeded by limited penetration depth towards the pectoral muscle, which is a frequently occurring challenge.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of breast MRI studies at 7 T have been presented with various RF coil setups . Although imaging performance in the anterior part of the breast is generally good, clinical usability might be impeded by limited penetration depth towards the pectoral muscle, which is a frequently occurring challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Phantom studies showed very good agreement in terms of the B 1 + field distribution as well as intensity. B 1 + field distributions/intensities in four breast models and Bphantom were highly consistent and were compared to that of other published high field numerical studies in the breast tissues [10, 31, 34]. Brown et al (Ref.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally while many high field breast MRI studies published promising results [1, 1013, 28–33]; to our knowledge, so far, only one study has evaluated B 1 + field and peak/average SAR variations in different breast models and compared to breast phantoms [34]. In our study, numerical analysis was performed using FDTD method in a homogeneous spherical model and in four different breast models.…”
Section: Introductionmentioning
confidence: 99%
“…[2328] Recognizing the need for anatomically-correct heterogeneous breast phantoms in conjunction with whole body voxel models, van der Velden et al fused a body model with 3D image data acquired from five healthy volunteers and ultimately noted that the observed disparity of simulated SAR distributions among these models was due to indeterminate variations in size and tissue makeup. [29] Breast size and tissue density have great variability among the patient population; to classify the extent of breast tissue density across women, radiologists largely have embraced the four tissue composition categories prescribed by the American College of Radiology (ACR) in the Breast Imaging Reporting and Data System (BI-RADS ® ). [30] Using this method, breast density is defined as (a) almost entirely fat, (b) scattered fibroglandular tissue, (c) heterogeneous fibroglandular tissue, and (d) extreme fibroglandular tissue.…”
Section: Introductionmentioning
confidence: 99%